Pengaruh kadar Kalsium Karbonat dalam kapur terhadap kepadatan badan keramik - Cingah, Made (Jurnal Energi Dan Manufaktur; Vol 2, No.1 Juni 2007)
The paper reported the experimental study on the influence of calcium carbonate content (CaCO3) in limestone to density of ceramic body. The density was measured in term of water absorption (Peresapan Air, PA) and pseudo porosity (Keporian Semu, KS). The Calcium carbonate content in limestone was determined by heating at temperature 1000oC and decomposing with acetate acid 25 %. The result indicated that both methods had no significantly different result. In addition, the two type limestones from different minefield had different CaCO3 contents. The limestone with higher CaCO3 content resulted in greater value of PA and KS of the ceramic body. The use of heated limestone (until 1000 oC) increased the density (decreased the PA and KS).
Keywords: Limestone, Calcium Carbonate, Calcium Oxide, density